Ionic liquid-based microwave-assisted extraction of essential oil and biphenyl cyclooctene lignans from Schisandra chinensis Baill fruits - Ma, Chun-hui; Liu, Ting-ting; Yang, Lei; Zu, Yuan-gang; Chen, Xiaoqiang; Zhang, Lin; Zhang, Ying; Zhao, Chunjian (Journal of Chromatography A, 2011)
► Application of ionic liquid-based microwave extraction. ► Extract essential oil and biphenyl cyclooctene lignans at one step. ► Four kinds of biphenyl cyclooctene lignans were simultaneously analyzed by HPLC. ► Composition of essential oil was analyzed by GC–MS. Ionic liquid-based microwave-assisted extraction (ILMAE) has been successfully applied in extracting essential oil and four kinds of biphenyl cyclooctene lignans from Schisandra chinensis Baill. 0.25 M 1-lauryl-3-methylimidazolium bromide ionic liquid is selected as solvent. The optimum parameters of dealing with 25.0 g sample are 385 W irradiation power, 40 min microwave extraction time and 1:12 solid–liquid ratio. The yields of essential oil and lignans are 12.12 ± 0.37 ml/kg and 250.2 ± 38.2 mg/kg under the optimum conditions. The composition of the essential oil extracted by hydro-distillation, steam-distillation and ILMAE is analyzed by GC–MS. With ILMAE method, the energy consumption time has not only been shortened to 40 min (hydro-distillation 3.0 h for extracting essential oil and reflux extraction 4.0 h for extracting lignans, respectively), but also the extraction efficiency has been improved (extraction of lignans and distillation of essential oil at the same time) and reduces the environmental pollution. S. chinensis materials treated by different methods are observed by scanning electronic microscopy. Micrographs provide more evidence to prove that ILMAE is a better and faster method. The experimental results also indicate that ILMAE is a simple and efficient technique for sample preparation.